The Effectiveness of the Role of the Office of Religious Affairs in Combating Early Marriage: A Case Study of Kandis Subdistrict - Muhammad Iran Simbolon; Ahmad Rofi'i Harahap; Parlindungan Simbolon (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2025)
Early marriage remains a significant problem in Kandis Subdistrict and has an impact on education, reproductive health, and the socio-economic stability of families. This study aims to analyze the effectiveness of the role of the Kandis Subdistrict Religious Affairs Office (KUA) in combating the practice of early marriage and to identify the supporting and inhibiting factors. This study uses a qualitative-descriptive approach through in-depth interviews with religious leaders, religious counselors, community leaders, parents, and adolescents, accompanied by observation and review of administrative documents. The results of the study show that the KUA has three strategic roles in preventing early marriage: (1) a regulatory role through age verification and marriage dispensation recommendations; (2) an educational role through the Marriage Guidance (Bimwin) program, youth counseling, and dissemination of marriage laws; and (3) an advocacy role through collaboration with schools, traditional leaders, and the DP3A agency. However, the effectiveness of these roles is still hampered by local cultural factors that consider early marriage to be normal, the community's lack of legal literacy, and the KUA's limited human resources and budget. This study emphasizes the need to strengthen the capacity of counselors, improve institutional synergy, and strengthen continuous legal education to minimize the practice of early marriage in Kandis District